The world almanac and book of facts 2016 - 20160731 frey50; Janssen, Sarah, 1982- (New York World Almanac Books, 2016)
Presents a reference with comprehensive facts and statistics on current events, people, and the countries of the world, along with original articles on recent issues and topics.
Includes indexes.
Keywords: Almanacs, American; United States